2000
DOI: 10.1007/bf02505413
|View full text |Cite
|
Sign up to set email alerts
|

Gas chromatographic enantiomer separation on single and mixed cyclodextrin derivative chiral stationary phases

Abstract: SummaryCapillary gas chromatographic enantiomer separation of some polar compounds, including a-phenylethylamine, styrene oxide, pyrethroid insecticides and other carboxylates, was investigated on modified cyclodextrin (CD) chiral stationary phases. The chiral stationary phases studied included permethylated fl-CD (PMBCD), hep-(DNTBCD), the mixture of PMBCD and DBBBCD, and the mixture of PMBCD and DNTBCD. On the mixed chiral stationary phases containing the mixtures ofderivatized cyctodextrins, enantiomer sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 17 publications
(11 reference statements)
0
10
0
Order By: Relevance
“…1,2 Nie et al 1 reported on the enantioseparation of chiral pyrethroid insecticides using a mixture of heptakis(2,3,6-tri-O-methyl)-β-cyclodextrin, with either heptakis (2,6-…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Nie et al 1 reported on the enantioseparation of chiral pyrethroid insecticides using a mixture of heptakis(2,3,6-tri-O-methyl)-β-cyclodextrin, with either heptakis (2,6-…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, in a number of papers the use of mixed binary CD selector systems for the enantioseparation of different classes of chiral compounds has been described [29][30][31][32][33][34][35]. In the present work, a comprehensive enantioselectivity spectrum toward racemic unfunctionalized alkanes and racemic derivatized ␣-amino acids as well as to other classes of racemic compounds such as lactones, diols, secondary alcohols, ketones and terpenes has been realized by diluting the two versatile CD selectors depicted in Fig.…”
Section: Resultsmentioning
confidence: 88%
“…Although, a larger cyclodextrin ring does not automatically mean improved separation when the size of the analyte is increased (Juvancz and Petersson 1996). Another alternative is to use a column with a mixture of different chiral phases, which has shown to significantly improve separation of some esters compared to single cyclodextrin derivative phases (Nie et al 2000). The combination of two different columns in the tandem techniques of heart cutting or two-dimensional GC (GC Ã GC) could also be a solution that needs to be investigated further (McNair and Miller 2009;Wang et al 2010).…”
Section: Separation Experimentsmentioning
confidence: 99%